Unusual Giant Syringomyelia with Neurocutaneous Melanosis - Shrestha, R; Cohen, AR (Journal of Nepal Paediatric Society, 2015)
A two year old male presented with feeding intolerance and lethargy. Mother had normal delivery with term baby. The patient denied previous trauma or recent weight loss. Physical examination revealed neurocutaneous melanosis (NCM) over lower back side of body and no signs of peripheral motor deficit or abnormal reflexes. Hematological investigations showed no abnormality. Magnetic resonance (MR) imaging found a large, cystic cavity that was eccentric in the cervicothoracic spine extending from C3 to L1. Suboccipital decompressive craniectomy, bilateral C1 laminectomy, and occipital duraplasty were done. J Nepal Paediatr Soc 2014;34(3):250-251 DOI: http://dx.doi.org/10.3126/jnps.v34i3.11165